Public Passenger Transport Service in Regions - Pavel Surovec (Communications - Scientific letters of the University of Zilina, 2002)
Public passenger transport aim is to provide transport service in a given region to ensure connection for inhabitants in villages and periphery with the center of economic, social, educational and cultural activities. The paper deals with the results of the study “C 519/2/HÚ1/1.6. Public Road Passenger Transport in a solved area”. The definition of public passenger transport service has been created using collected land use and transport data from Žilina region. The definition is very important for financing public transport from state, regional governments and communities’ budgets because of covering documentary loss probability.